1999
DOI: 10.1021/jp9843095
|View full text |Cite
|
Sign up to set email alerts
|

Rotation of Aromatic Hydrocarbons in Viscous Alkanes. 2. Hindered Rotation in Squalane

Abstract: Time-resolved single-photon counting and the synchrotron radiation source at the CCLRC’s Daresbury Laboratory have been used to measure the decay of fluorescence anisotropy of solutions in squalane of the aromatic hydrocarbons triphenylene, coronene, benzoperylene, perylene, anthracene, and tetracene. For the last four, extra information was obtained by exciting both parallel and perpendicular to the fluorescence transition. The results differ markedly from those obtained in methylcyclohexane (part 1 of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 48 publications
3
14
0
Order By: Relevance
“…Coronene has D 6 h symmetry; the others resemble anthracene. (Benzoperylene is included here and in Tables1 and 2 though it has been studied only in squalane …”
Section: Theory and Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Coronene has D 6 h symmetry; the others resemble anthracene. (Benzoperylene is included here and in Tables1 and 2 though it has been studied only in squalane …”
Section: Theory and Backgroundmentioning
confidence: 99%
“…These results are reported here and compared to data for the same solutes in other solvents. In squalane, new phenomena are found that can be described in terms of limited range rotation and the α and β processes used to intepret relaxation near the glass transition; these are reported in the following paper . The earlier work has been extended in two ways: solutes have been excited at two different wavelengths and a wider range has been used.…”
Section: Theory and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Squalane has been studied in molecular dynamics simulations of nonlinear flows [19]. Squalane has also been used as a solvent for studying the intriguing Debye dielectric relaxation of mono-hydroxy alcohols [20], the rotation of aromatic hydrocarbons in viscous alkanes [21], and the Stokes-Einstein relation for diffusion of organic solutes [22]. Due to its low vapor pressure squalane is used as a benchmark molecule for reaction-dynamics experiments performed under ultrahigh vacuum [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] These investigations have provided a wealth of information on how the relative size of the solute to the solvent affects the reorientation time by altering the boundary condition parameter and also how the rotation of the solute is influenced by the free volume of the solvent. In such a scenario, Stokes-Einstein-Debye ͑SED͒ hydrodynamic theory 1,2 with slip boundary condition is more or less adequate to account for the rotational relaxation of a solute molecule.…”
Section: Introductionmentioning
confidence: 99%